Petrography and geochemistry of the Paleocene sandstones from north of Birjand: Implications for provenance, tectonic setting and paleoclimate conditions - Zahra Hasani; Maryam Mortazavi Mehrizi; Seyed Nasser Raeisosadat (Journal of Stratigraphy and Sedimentology Researches, 2018)
Introduction